ANALISIS KURANGNYA MINAT MAHASISWA MEMILIH PROGRAM STUDI PENDIDIKAN BAHASA ARAB DI STAIN DATOKARAMA PALU - Kasmiati Kasmiati (Hunafa: Jurnal Studia Islamika, 2009)
This research deals with the lack of  interest of the students in Arabic Language Teaching Program at STAIN Datokarama Palu. This research is intended to describe the factors that make the students have low in interest in Arabic Teachiung Program. The results shows that decreasing interest is much more associated with (1) the lack of opportunity to find jobs, especially to be civil servants; (2) the influence their counterparts to make a similar choice; and (3) the deminishing promotion of this program to the prospective students. The efforts have to be made in order to get much more students are incessant promotion of this program to public, intensive Arabic preparation for students and curriculum improvement.Kata Kunci:    minat, pendidikan bahasa Arab, sosialiasi, lapangan kerja